Pregunta
upstudy study bank question image url

and \( x y=21 \) find \( x^{3}+y^{3} \) \( x^{3}+y^{3}=(x+y) \)

Ask by Lindsey Watkins. in India
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

To find \( x^{3} + y^{3} \) given that \( xy = 21 \), you need to know the value of \( x + y \). The formula is: \[ x^{3} + y^{3} = (x + y)^3 - 63(x + y) \] Without \( x + y \), you can't find a specific value for \( x^{3} + y^{3} \).

Solución

It seems you're looking to find \( x^{3} + y^{3} \) given that \( xy = 21 \). To determine \( x^{3} + y^{3} \), additional information about the sum \( x + y \) is typically required. However, I can provide you with a general formula that relates these expressions. ### Formula for \( x^{3} + y^{3} \) The sum of cubes can be expressed in terms of \( x + y \) and \( xy \) using the following identity: \[ x^{3} + y^{3} = (x + y)^3 - 3xy(x + y) \] ### Applying the Given Information Given: \[ xy = 21 \] Plugging this into the formula: \[ x^{3} + y^{3} = (x + y)^3 - 3 \times 21 \times (x + y) \] \[ x^{3} + y^{3} = (x + y)^3 - 63(x + y) \] ### What You Need Next To find a numerical value for \( x^{3} + y^{3} \), you need to know the value of \( x + y \). If you have that information, you can substitute it into the equation above to compute \( x^{3} + y^{3} \). ### Example **Suppose** \( x + y = 6 \): \[ x^{3} + y^{3} = 6^3 - 63 \times 6 = 216 - 378 = -162 \] **However**, if you don't have \( x + y \), you can only express \( x^{3} + y^{3} \) in terms of \( x + y \) as shown above. --- **Summary:** Given \( xy = 21 \), the expression for \( x^{3} + y^{3} \) in terms of \( x + y \) is: \[ x^{3} + y^{3} = (x + y)^3 - 63(x + y) \] If you can provide or determine \( x + y \), you can then calculate a specific value for \( x^{3} + y^{3} \).

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To find \( x^3 + y^3 \), we can use the identity \( x^3 + y^3 = (x + y)(x^2 - xy + y^2) \). Given that \( xy = 21 \), we need to find \( x + y \) first. Let's denote \( s = x + y \) and \( p = xy \). The quadratic equation formed is \( t^2 - st + p = 0 \). The roots will yield \( x \) and \( y \). Once we have \( s \), we can compute \( x^2 + y^2 \) using \( x^2 + y^2 = (x + y)^2 - 2xy = s^2 - 2p \). Then we can easily substitute these values into the identity to solve for \( x^3 + y^3 \)! Now let's say \( s = 7 \) (for example), then \( x^2 + y^2 = 7^2 - 2(21) = 49 - 42 = 7 \). Thus, \( x^3 + y^3 = 7(7 - 21 + 7) = 7(7 - 21 + 7) = 7(-7) = -49 \). If you have actual values for \( x \) and \( y \) that fit \( xy = 21 \), plug those into the formulas to calculate \( x^3 + y^3 \)!

preguntas relacionadas

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad